New Testament Apocrypha / volume 1 - Burke, Tony; Landau, Brent (New Testament Apocrypha more noncanonical scriptures, 2016)
"Compilation of little-known and never-before-published apocryphal Christian texts in English translation This anthology of ancient nonbiblical Christian literature presents introductions to and translations of little-known apocryphal texts from a wide variety of genres, most of which have never before been translated into any modern language. An introduction to the volume as a whole addresses the most significant features of the included writings and contextualizes them within the contemporary (quickly evolving) study of the Christian Apocrypha. The body of the book comprises thirty texts that have been carefully introduced, annotated, and translated into readable English by eminent scholars. Ranging from the second century to early in the second millennium, these fascinating texts provide a more complete picture of Christian thought and expression than canonical texts alone can offer"--